Clinical use of HD-MTX monotherapy in a rare case of refractory primary bone diffuse large B-cell lymphoma with long-term survival after local radiotherapy: A case report - Wu, Zhiya; Teng, Yue; Wu, Jianqiu; Zhang, Honglu; Peng, Weiwei; Meng, Cheng; Tang, Weiyan; Feng, Jifeng (Frontiers in Medicine, 2022)
Primary bone diffuse large B-cell lymphoma (PB-DLBCL) has been rarely reported because of its low incidence. The optimal treatment plan for patients with relapsed/refractory PB-DLBCL remains controversial. Now we present a 57-year-old patient of refractory PB-DLBCL to better understand this disease. The patient developed lumbosacral/low extremities pain. Lumbar MRI (magnetic resonance imaging) revealed skeletal lesions with osteolysis in L4-5, S1. With the failure of multi-line chemotherapy, the patient developed paralysis of both lower limbs. 18-fluorinefluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) and MRI showed new lesions in the femoral head, cervical and thoracic vertebrae. We tried to treat patient with adjuvant radiotherapy and ten courses of high-dose methotrexate-based (HD-MTX) monotherapy which helped her recover the walking ability and receive complete remission (CR). To our knowledge, it is the first attempt to use local radiotherapy combined with HD-MTX regimen successfully for the treatment of refractory PB-DLBCL.